2016
DOI: 10.1111/jace.14263
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon Carbide Nanocrystals Using Waste Poly(vinyl butyral) Sheet

Abstract: SiC nanocrystals were prepared using waste poly(vinyl butyral) sheet as a carbon source. SiO 2 /poly(vinyl butyral) mixtures are converted to SiO 2 /pyrolytic carbon composites via pyrolysis at low temperatures (500°C) in an Ar atmosphere. Subsequently, low-temperature magnesiothermic reduction and purification processes result in the formation of tiny SiC nanocrystals. The size of the synthesized SiC nanocrystals ranged from 3 to 12 nm, i.e., they are smaller than the SiO 2 precursor offering large specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Microstructural changes were also investigated as a function of the phosphidation temperature, as shown in Figure 2B to E. SEM images of as‐prepared Ni NPs demonstrated that very small nanoparticles were aggregated with each other because of the strong surface energy of nano‐size materials 32,34 . Ni 2 P‐400 exhibited relatively bulky particles agglomerated by thermal phosphidation at 400°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructural changes were also investigated as a function of the phosphidation temperature, as shown in Figure 2B to E. SEM images of as‐prepared Ni NPs demonstrated that very small nanoparticles were aggregated with each other because of the strong surface energy of nano‐size materials 32,34 . Ni 2 P‐400 exhibited relatively bulky particles agglomerated by thermal phosphidation at 400°C.…”
Section: Resultsmentioning
confidence: 99%
“…Microstructural changes were also investigated as a function of the phosphidation temperature, as shown in Figure 2B to E. SEM images of as-prepared Ni NPs demonstrated that very small nanoparticles were aggregated with each other because of the strong surface energy of nano-size materials. 32,34 Ni 2 P-400 exhibited relatively bulky particles agglomerated by thermal phosphidation at 400 C. Upon increasing the phosphidation temperature from 400 C to 600 C, the initial Ni NPs were extremely agglomerated and sintered with each other, resulting in massive Ni 2 P particles.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Figure 5 shows the corresponding EDS analysis of the detected point on the W particle of the green tape with SiC particle size of 10 µm after debinding and thermal treatment. It detects not only W but also a small amount of C, which reveals that organic additives kept in surface of tungsten converted into pyrolytic carbon coating [21].
Figure 5 (a) SEM micrograph of the W-SiC/Cu green tape with SiC particle size of 10 µm after debinding and thermal treatment, (b) EDS results of the detected point.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the corresponding EDS analysis of the detected point on the W particle of the green tape with SiC particle size of 10 μm after debinding and thermal treatment. It detects not only W but also a small amount of C, which reveals that organic additives kept in surface of tungsten converted into pyrolytic carbon coating [21].…”
Section: Microstructuresmentioning
confidence: 99%
“…Rajarao et al (2014) [211] and Maroufi et al (2017)[212] have also recycled electronic waste as a C source and e-waste glass source of SiO 2 , respectively, for preparing SiC Qadri et al (2015) [213]. have prepared SiC through the pyrolysis of the husks, stalks, leaves, and cob residues of corn plant above 1450°C in an inert atmosphere Park et al (2016) [214]. have synthesized nano SiC (3-12 nm) via lowtemperature pyrolysis (500°C) and magnesiothermic (650°C) of SiO 2 /waste poly(vinyl butyral) mixtures in an Ar atmosphere Gubernat et al (2017) [215].…”
mentioning
confidence: 99%